Edit at will: Genotype independent plant transformation in the era of advanced genomics and genome editing. (April 2019) - Kausch, Albert P.; Nelson-Vasilchik, Kimberly; Hague, Joel; Mookkan, Muruganantham; Quemada, Hector; Dellaporta, Stephen; Fragoso, Christopher; Zhang, Zhanyuan J.
Highlights: Advanced genomics has allowed sequence and gene identification. Genome editing presents the possibility for functional genomics. New technologies for plant transformation enable actualization. The ability to 'edit at will' profoundly changes plant biology and agriculture. Abstract: The combination of advanced genomics, genome editing and plant transformation biology presents a powerful platform for basic plant research and crop improvement. Together these advances provide the tools to identify genes as targets for direct editing as single base pair changes, deletions, insertions and site specific homologous recombination. Recent breakthrough technologies using morphogenic regulators in plant transformation creates the ability to introduce reagents specific toward their identified targets and recover stably transformed and/or edited plants which are genotype independent. These technologies enable the possibility to alter a trait in any variety, without genetic disruption which would require subsequent extensive breeding, but rather to deliver the same variety with one trait changed. Regulatory issues regarding this technology will predicate how broadly these technologies will be implemented. In addition, education will play a crucial role for positive public acceptance. Taken together these technologies comprise a platform for advanced breeding which is an imperative for future world food security.